Teacher Strategies in Numeracy Learning for Students in Elementary School - Yantoro, Yantoro; Hayati, Suci; Wilutama, Anggita Harely (Pedagogik Journal of Islamic Elementary School, 2020)
This study aims to describe the teacher's strategy in learning multiplication of student multiplication in class III C SD Negeri 19 / IV Jambi City. This research was conducted at the 19 / IV Public Elementary School in Jambi City in the even semester of the 2019/2020 school year. This research was a phenomenological research with a qualitative approach. The qualitative approach in this study uses interview and documentation instruments using the Miles and Huberman technique. Data analysis is performed by data reduction, data presentation, and data vertification and conclusions. The data obtained in the form of qualitative data that contains a description of the results of interviews with teachers about the teacher's strategy in learning the multiplication of students in class III C SD Negeri 19 / IV Jambi City. The results showed that the teacher used several learning strategies including learning strategies that were centered on the instructor, learning strategies that were centered on students, heuristic or kuriorstic learning strategies, induction learning strategies. Then the obstacle encountered by the teacher is related to multiplication counting which is difficult to memorize multiplication, the child who has difficulty counting multiplication, the teacher will order the child to repeat his memorization again.